Tax Cut: Suatu Studi Literatur - Utami Tunjung Sari; Niken Permata Sari; Hananta Surya Wijaya (Accounting and Finance Studies, 2021)
This study aims to determine the factors associated with the tax cut. The literature review method was used in this study. The data in this study were obtained from sciencedirect.com. The results showed that several variables were influential and influenced by tax cuts, as well as variables that had no effect. The results show that the tax cut has no significant effect on median weekly earnings, has a significant effect on merger activity, shareholder wealth, distribution economic activity, aggregate welfare, R&D investment, domestic market shares and exports, investment, employment, profit, tax revenue, gross domestic product, inbound tourism, and travel receipts, as well as labor supply and consumption decisions. There are several conflicting research results due to differences in the place of study and the time period of the study which resulted in different conclusions. The tax cut is also influenced by government debt. An overview of further research is also presented here.